2015
DOI: 10.2527/jas.2014-8471
|View full text |Cite
|
Sign up to set email alerts
|

Feed restriction and realimentation in Holstein–Friesian bulls: II. Effect on blood pressure and systemic concentrations of metabolites and metabolic hormones1

Abstract: The objective of this study was to evaluate the endocrine response and metabolic rate in Holstein–Friesian bulls during restricted feeding and realimentation. Sixty bulls were allocated to 1 of 2 feeding regimes: 1) restricted feed allowance (RES; n = 30) or 2) ad libitum feeding (ADLIB; n = 30) for 125 d (Period 1). The bulls in both treatment groups were then offered ad libitum access to feed for a further 55 d (Period 2). Five and 4 blood samples were collected during periods 1 (n = 60) and 2 (n = 30), resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
46
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(61 citation statements)
references
References 45 publications
12
46
3
Order By: Relevance
“…Alternatively, it has been suggested that the immune response could be involved in nutrient partitioning away from non-essential activities including growth and instead towards activating tissue mobilisation and catabolism [72]. Nutrient partitioning during diet restriction has been widely reported in cattle [11, 12, 44, 73, 74]. When coupled with data from the present study these results indicate that the immune system may be contributing to this observed effect.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Alternatively, it has been suggested that the immune response could be involved in nutrient partitioning away from non-essential activities including growth and instead towards activating tissue mobilisation and catabolism [72]. Nutrient partitioning during diet restriction has been widely reported in cattle [11, 12, 44, 73, 74]. When coupled with data from the present study these results indicate that the immune system may be contributing to this observed effect.…”
Section: Discussionsupporting
confidence: 70%
“…Both of these genes were also up-regulated in skeletal muscle tissue of cattle undergoing CG [25]. Overall these results suggest that increased cellular protein folding activity is required within the rumen papillae as part of the adaption to an increased dietary intake and is consistent with the heightened metabolic state typical of animals undergoing re-alimentation induced CG [11, 12, 44, 45]. Indeed, this may be a necessary response in order to cope with the typically elevated rate of metabolism associated with greater feed consumption [46], which appears to be a primary driver of whole animal CG [8, 11, 14].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The increased urine creatinine concentration as tannin was added could be linked to a likely increase in muscle catabolism to compensate for the lower dry matter intake (Keogh et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…It may be defined as a physiological process whereby an animal has the potential, following a period of restricted feed intake, to undergo accelerated growth upon re-alimentation (31). Previous investigations into the underlying biology of compensatory growth by our own group and by others have suggested greater feed intake and efficiency, reduced metabolic rate, and alterations in energy partitioning and tissue deposition to all be associated with the accelerated growth phenomenon (31,37,62,64,77,78). However, despite its potential importance to reducing the costs of beef cattle production systems, there is a dearth of knowledge in relation to the biological and in par-ticular the molecular mechanisms regulating the compensatory growth phenomenon.…”
mentioning
confidence: 99%